2017
DOI: 10.7554/elife.18422
|View full text |Cite|
|
Sign up to set email alerts
|

Perceptual decisions are biased by the cost to act

Abstract: Perceptual decisions are classically thought to depend mainly on the stimulus characteristics, probability and associated reward. However, in many cases, the motor response is considered to be a neutral output channel that only reflects the upstream decision. Contrary to this view, we show that perceptual decisions can be recursively influenced by the physical resistance applied to the response. When participants reported the direction of the visual motion by left or right manual reaching movement with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 45 publications
5
102
1
Order By: Relevance
“…Recently, it has been shown that perceptual decisions were biased by the amount of motor effort it took for participants to make the response (Hagura et al 2017). In this study, participants' decision was biased towards the least effortful motor response.…”
Section: Motor Activity and Metacognitionmentioning
confidence: 75%
“…Recently, it has been shown that perceptual decisions were biased by the amount of motor effort it took for participants to make the response (Hagura et al 2017). In this study, participants' decision was biased towards the least effortful motor response.…”
Section: Motor Activity and Metacognitionmentioning
confidence: 75%
“…Studies show that when the motor costs associated with redirection are increased (through distance or force fields), changes of mind become more infrequent. Motor costs can even affect perceptual decision making when participants are unaware of them (i.e., when they are introduced very gradually), and these can bias verbal reports of perceptual discriminations, even when they are conveyed through a completely different effector system . Together, this work indicates that the motor system, rather than merely reflecting the output of upstream perceptual processing, can itself influence perceptual processes and the transformation into decision space.…”
Section: Action‐based Models: From Reaction Time To End Of Movementmentioning
confidence: 83%
“…This theory can explain how decisions can be made between both actions and abstract values. 131 Furthermore, recent evidence suggests that competition can indeed occur at both good-and action-based representations, 158 and that these might share strong reciprocal connections 98,104 (but see, Ref. 158).…”
Section: Conclusion and Extensionsmentioning
confidence: 99%
“…showed that motor costs also bias vocally-expressed judgments, suggesting that actions changed 566 how subjects perceived the stimuli themselves (Hagura et al, 2017). 567…”
Section: Motor Costs Influence Motor and Perceptual Decision-making 534mentioning
confidence: 99%